Uncovering the Factors That Influence the Public to Spread Infodemic in Indonesia - Widyatama, Rendra; Adiprabowo, Vani Dias; Ananda, Vidya; Paderan, Mark (Universitas Ahmad Dahlan, 2023)
This study aims to explain factors that influence people to continue disseminating the infodemic even when they have a high level of education. This research uses a qualitative approach with data mined using interview techniques and literature studies. The qualitative research gathered data through in-depth online interviews and literature studies. Key informants, including experts in Communication Science, Religion, Social Media, and Health, were interviewed using semi-structured interviews, allowing for flexible yet focused discussions. The study's findings identify 12 factors contributing to the continued spread of the infodemic, including social media ownership, a critical attitude towards information, information-seeking skills, emotional maturity in processing information, the demands of daily life, the frequency of social media use, social media friend networks, efforts to enhance digital literacy, a tendency to avoid seeking information clarification, a narrow interpretation of religious teachings, belief in conspiracy theories, and specific underlying motives. This research contributes significantly by shedding light on this pressing issue, offering insights crucial for formulating evidence-based policies and interventions to enhance digital literacy and effectively counter the infodemic. Future researchers should concentrate on investigating motive aspects. Moreover, rigorous statistical tests in quantitative research can also be considered to enhance the depth of analysis, providing a quantitative measure of the influence exerted by each identified factor.